Investigation on the mutation of PPP2R3A exons in retinoblastoma - Hui Wang (Guoji Yanke Zazhi, 2017)
AIM:To explore the association of the mutation in PPP2R3A exons and retinoblastoma. METHODS: Hospital-based case control study was taken. Retinoblastoma patients(15 cases, as case group)and matched controls(30 controls, as control group)were recruited in this study. Genomic DNA obtained from formalin fixed paraffin embedded(FFPE)and peripheral blood were used as template. PPP2R3A gene exon sequences were detected by PCR-sequencing. Homology analysis was performed using blastn in GenBank. RESULTS: Analyzing PPP2R3A DNA sequences(1001bp)from 15 cases, two reported SNPs had been detected, including rs34629706 and rs144802055. Rs34629706 also occurred in the control group. Rs144802055 appeared only in the case group. CONCLUSION: PPP2R3A gene SNPs of rs34629706 is unrelated to the incidence of retinoblastoma. Relations between rs144802055 and RB needs to be further explored.